A note on the spaces θM and θ′M - Carlos Bosch (International Journal of Mathematics and Mathematical Sciences, 1988)
The spaces θM and θ′C of multiplication and convolution operators on temperate distributions, together with their strong duals θ′M and θC, are Montel and distinguished.